Pendampingan Belajar Iqro’ Berbasis Media Flashcard Sebagai Upaya Menumbuhkan Cinta Al-Qur’an Sejak Usia Prasekolah - Yunita Sari; Jupriyanto; Muhamad Afandi; Nurfatanah (Pusmedia Group Indonesia, 2026)
This community service activity aims to improve Iqro' reading skills through flashcard-based learning assistance. The problem that occurs is that Iqro' learning that has been implemented so far still focuses on reading and writing activities without being supported by interesting learning media. This condition causes children to tend to quickly feel bored and less motivated in participating in the learning process. The implementation method uses a Service-Learning approach which includes preparation, implementation, reflection, and evaluation stages. The subjects of the activity consisted of 40 early childhood students. The results of the activity implementation showed an increase in Iqro' reading skills as indicated by an increase in the average pretest score of 61 to 83 on the posttest. In addition, the results of the student satisfaction response questionnaire obtained a score of 93.2% with a very good category. The conclusion shows that flashcard-based Iqro' reading learning assistance is effective in improving Iqro' reading skills, learning motivation, and providing a pleasant learning experience for students.